2015
DOI: 10.1523/jneurosci.4841-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Complexin Stabilizes Newly Primed Synaptic Vesicles and Prevents Their Premature Fusion at the Mouse Calyx of Held Synapse

Abstract: Complexins (Cplxs) are small synaptic proteins that cooperate with SNARE-complexes in the control of synaptic vesicle (SV) fusion. Studies involving genetic mutation, knock-down, or knock-out indicated two key functions of Cplx that are not mutually exclusive but cannot easily be reconciled, one in facilitating SV fusion, and one in "clamping" SVs to prevent premature fusion. Most studies on the role of Cplxs in mammalian synapse function have relied on cultured neurons, heterologous expression systems, or mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(67 citation statements)
references
References 83 publications
9
58
0
Order By: Relevance
“…Loss-of-function studies have indicated inhibitory and facilitatory activities of Cplxs in SNARE-mediated vesicle fusion and distinct Cplx domains were suggested to be responsible for the opposing functions (Xue et al, 2007;Maximov et al, 2009;Kaeser-Woo et al, 2012;Yang et al, 2013;Lai et al, 2014;Chang et al, 2015; for review see Trimbuch and Rosenmund, 2016). Although most of our knowledge about Cplx function stems from studies on Cplx1 and Cplx2 present at conventional brain synapses, little is known about Cplx function at sensory synapses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function studies have indicated inhibitory and facilitatory activities of Cplxs in SNARE-mediated vesicle fusion and distinct Cplx domains were suggested to be responsible for the opposing functions (Xue et al, 2007;Maximov et al, 2009;Kaeser-Woo et al, 2012;Yang et al, 2013;Lai et al, 2014;Chang et al, 2015; for review see Trimbuch and Rosenmund, 2016). Although most of our knowledge about Cplx function stems from studies on Cplx1 and Cplx2 present at conventional brain synapses, little is known about Cplx function at sensory synapses.…”
Section: Discussionmentioning
confidence: 99%
“…In the mouse auditory system, Cplxs were not detected in cochlear hair cells, but Cplx1 was found in spiral ganglion neurons and at the end bulb of Held in the cochlear nucleus (Strenzke et al, 2009;Chang et al, 2015). In the mouse retina, all four Cplx isoforms were detected with Cplx3 and Cplx4 present at photoreceptor ribbon synapses (Reim et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Cplxs appear to suppress spontaneous exocytosis and, thereby, preserve vesicles in a release-ready state (Chang et al, 2015; Rizo and Xu, 2015). Therefore, we recorded spontaneous, AMPAR-mediated EPSCs in AIIs in the presence of L-AP4, a mGluR6 agonist that hyperpolarizes presynaptic RBs and reduces spontaneous EPSC frequency; spontaneous EPSCs in this condition are presumed to be quantal, miniature EPSCs (mEPSCs) (Jarsky et al, 2010; Mehta et al, 2013; Singer et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Several recent studies described perturbations, either pharmacological or genetic, which change the synaptic release probability in the absence of changes in Ca 2+ current, [Ca 2+ ] i dynamics, and SV pool sizes (8,(49)(50)(51). Whereas changes in the latter parameters are well understood and have been recognized as strong modulators of transmitter release, the mechanisms underlying differences in "intrinsic" release readiness have received less attention.…”
Section: Discussionmentioning
confidence: 99%